2012
DOI: 10.1103/physrevb.85.085417
|View full text |Cite
|
Sign up to set email alerts
|

Observation of linear solid-solid phase transformation in silicon nanoparticles

Abstract: In bulk single crystal silicon, the semiconducting diamond to metallic ß-Sn phase transformation nucleates on defects, and is manifested by a sharp uptake in light absorption at a threshold of ~ 11 Gpa, accompanied with the creation of nanosized (20-50 nm) fragmentation domains. We report on the observation of linear uptakes in the absorption and in the luminescence, and with insignificant spectral change in ultrasmall 1 nm Si particles. We associate the gradual absorption uptake and luminescence yield with si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The excitation of the blue luminescence band indicates a two photon excitation process, while the second harmonic indicates the breaking of the centrosymmetry. Other theoretical simulations showed that the mechanical strain exerted is extremely high, corresponding to a pressure of several Gpa [40]. Because atoms on the surface are under high strain, they can undergo large-amplitude molecular-like vibrations to relieve the strain [41]; and hence can also couple efficiently to thermal and mechanical stimuli.…”
Section: Optical Nonlinearity In Nanosiliconmentioning
confidence: 99%
“…The excitation of the blue luminescence band indicates a two photon excitation process, while the second harmonic indicates the breaking of the centrosymmetry. Other theoretical simulations showed that the mechanical strain exerted is extremely high, corresponding to a pressure of several Gpa [40]. Because atoms on the surface are under high strain, they can undergo large-amplitude molecular-like vibrations to relieve the strain [41]; and hence can also couple efficiently to thermal and mechanical stimuli.…”
Section: Optical Nonlinearity In Nanosiliconmentioning
confidence: 99%